Implementation of Android-based MSME Bookkeeping Applications Using the Buku Warung Application at CV Andi Windu - Masrizal, Masrizal; Meldona (JIMEK : Jurnal Ilmiah Mahasiswa Ekonomi, 2024)
Indonesia is a developing country, where developing countries focus on development and economic growth in a better direction. Micro, small and medium enterprises (MSMEs) are one type of business that contributes to economic growth and development in Indonesia. Micro, Small and Medium Enterprises (MSMEs) have an important role in a country's economy. They are a vital part of the economic sector, playing a major role in job creation. They are often the main providers of employment for local residents, including those with limited qualifications or work experience